Faktor-Faktor Yang Mempengaruhi Keputusan Konsumen Menggunakan Jasa Transportasi Berbasis Aplikasi Online Di Kota Denpasar - Ni Kadek Erra Wahyuni (Jurnal Akuntansi Profesi, 2019)
The reseach was aimed to find out the factors affecting consumer decisions and the most dominant factor affecting consumer decisions using the services of online-based transport applications in the city of Denpasar. This type of research is factorial research. The population in this research is the whole community that is in the area of Denpasar city that has used online transportation based. This research sample amounted to 97 respondents with incidental sampling methods. The data collection technique is done by spreading online questionnaire with Likert scale and processed using factor analysis technique. The results showed that there were fourteen factors influencing, namely distribution factors, learning factors, promotion factors, price factors, motivational factors, cultural factors, social class factors, family factors, demographic factors, factors Attitudes, perception factors, product factors, personality factors and group reference factors. The most dominant factor affecting consumers using online application-based transport services is the distribution factor with a factors rotation value of 52.283%, meaning the total value of the factors rotation of the distribution is able to explain the decision Consumers using online application-based transportation services in Denpasar City.